IMPACT OF LEAN AND AGILE SUPPLY CHAIN INDONESIA COFFEE TO SUSTAINABILITY STRATEGY MEDIATES BUSINESS STRATEGY (Proceedings of the International Conference on Poverty and Sustainable Development, 2019)
This paper aims to investigate sustainability strategy coffee processing industry companies in Indonesia and methods and goals associated with a different concept with the concept of developing management. This research to analyze the use of strategy lean and agile supply chain of Indonesian coffee's product's impact to business strategy and sustainability strategy and to maintain the Indonesian coffee plant to survive in the long term sustainable development. Indonesian coffee has a special uniqueness that is only available in Indonesia. The paper is based on a review of literature, both journal articles and books, and the result of observation on the coffee processing companies and farmers, and proposed a conceptual model. The cooperation between the manufacturer and buyer with the involvement of a partner stakeholder in the supply chain become a consideration as the focus of the company in managing their core competence and all other activities of outsourcing. Companies have made tough decisions about what and how operations, they must execute well and then applied. The data obtained from interviews and observed the 6 SME’s and 38 farmers in West Java. From these observations, furthermore, a positive relation is found between the use of lean and agile supply chain to the business strategy and then affect Indonesian coffee industry sustainability strategy.
Keywords: Lean Supply Chain; Agile Supply Chain; Business Strategy; Sustainability Strategy